PENCEGAHAN INFEKSI Aeromonas hydrophila PADA IKAN PATIN (Pangasius sp.) MENGGUNAKAN TEPUNG PACI-PACI (Leucas lavandulaefolia) DENGAN DOSIS YANG BERBEDA - Septika Putri Anggraini; Ade Dwi Sasanti; Marini Wijayanti (Jurnal Akuakultur Rawa Indonesia, 2017)
ABTRACT The aim of this research was to know the effect of paci-paci (L. lavandulaefolia) powder addition in feed suplemented for 14 days to the prevent A. hydrophila infection Pangasius sp. The research was conducted on August-September 2016 in Laboratorium Kolam Percobaan Budidaya Perairan, Aquaculture Study Program, Agriculture Faculty, Sriwijaya University and hematocrite examination was conducted in PMI Palembang. The research based on Completely Randomized Design (CRD) with six treatments and three replications. The fish was injected by A. hydrophila with density of 1,7x108 cfu.mL-1. The Pangasius sp. has been reared for 30 days and fed with pellet enriched  with 8%, 10%, 12 % and 14% Leucas lavandulaefolia  powder. Feeding frequency was four times a day. The parameters observed on this research were prevalence, hematocrite, survival, growth and water quality. The result showed that the addition the Laucas lavandulaefolia powder in feed effect on prevalence, survival rate and patin fish growth. The treatment that produced the best prevention was the addition of 12% Leucas lavandulaefolia powder in feed which produced 28.07% prevalence, 85.00% survival rate and 1.11 cm absolute length growth. Keywords: A. hydrophila, Pangasius sp, Dosage, Leucas lavandulaefolia,